DUKUNGAN KESEHATAN JIWA PSIKOSOSIAL TERHADAP RESILIENSI MASYARAKAT MENGHADAPI MASA PANDEMI COVID-19 - DIANA ARIANTI DIANA ARIANTI; Amelia Susanti (LPPM Universitas Abdurrab, 2022)
According to WHO (2020) the emergence of maniam pandemics causes stress in various communities. Although there has been no systematic review of the impact of COVID-19 on mental health, a number of studies related to bird flu and SARS panemi) have shown a negative impact on the mental health of sufferers. The purpose of this study is to know the Influence of Psychosocial Mental Health Support on Community Resilience Facing the Covid-19 Pandemic in Wiayah Kerja Puskesmas Kuranji Padang year 2020. This research is quantitative cross sectional design study. The sample in this study was 98 respondents. This research was conducted in kuranji padang health center area conducted in December to February 2021. The data used is primary data and secondary data. The results of the study obtained psychosocial mental health support to the pandemic from 98 respondents more than half who did not support (51.9%) while the supporting (40.9%). Psychosocial mental health support for the pandemic period from 98 respondents more than half who did not bow (59.1%) while the supporting (40.9%). Chi-Square statistical test results obtained P value 0.012 (P<0.05), it can be concluded that there is a significant link between psychosocial mental health support to the resilience of the community facing the covid-19 pandemic.